Melt‐Extrusion‐Based Additive Manufacturing of Transparent Fused Silica Glass (Adv. Sci. 23/2021). Issue 23 (8th December 2021) - Mader, Markus; Hambitzer, Leonhard; Schlautmann, Phillip; Jenne, Sophie; Greiner, Christian; Hirth, Florian; Helmer, Dorothea; Kotz‐Helmer, Frederik; Rapp, Bastian E.
Abstract : Melt‐Extrusion‐Based Additive Manufacturing Glass is of outmost importance for many applications in science, industry, and everyday life. In article number 2103180, Frederik Kotz‐Helmer and co‐workers present melt extrusion based additive manufacturing of thermoplastic nanocomposites which are subsequently converted to transparent fused silica glass. The cover shows Erlenmeyer flasks fabricated by this process.